LEGAL PROTECTION FOR EDUCATORS AS LECTURERS FOR OBTAINING LABOR RIGHTS - Mardayanti, Imelda; Hulu, Fonaha (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Legal protection for all workers/employees, especially for lecturers who work under foundations, is absolutely necessary, considering that there are still many cases involving universities and foundations. These problems still haunt lecturers, so there needs to be a joint effort to minimize existing problems. Even though there are already regulations governing the relationship between workers/laborers and employers, in practical terms they have not yet been fully implemented. This is related to several problems, one of which is the position of lecturers at the subordinate level more than the foundation. This phenomenon will not occur when educators take advantage of legal protection that has been regulated in legislation. This study will elaborate on legal protection for workers, especially for educators. The research method used is a normative juridical approach using a statutory approach. The result is legal protection for educators as stipulated in Law Number 21 of 2000 concerning Trade Unions, in particular regarding the purpose of the formation of trade unions. In addition, Law no. 13 of 2003 concerning Manpower has protected workers/employees, including educators, namely through trade unions/employees.